2019
DOI: 10.1002/chem.201805932
|View full text |Cite
|
Sign up to set email alerts
|

A Phosphorus Analogue of p‐Quinodimethane with a Planar P4 Ring: A Metal‐Free Diphosphorus Source

Abstract: Para-quinodimethane (pQDM) is af undamental structural component in many p-conjugated organic molecules andm aterials. The incorporation of phosphorus atom into p-conjugated frameworks offersu nique opportunitiesf or controlling the properties of derived species. A phosphorus analogueo fp-quinodimethane (pQDM), (IPrC) 2 P 4 [5,I Pr = C{N(Ar)CH 2 } 2 ;A r= 2,6-iPr 2 C 6 H 3 ]f eaturinga planar P 4 ring, was readily accessible by KC 8 -reduction of (IPrC)(PCl 2 ) 2 (2). Base-mediatedC ÀHf unctionalizationo f IPr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 54 publications
0
14
0
Order By: Relevance
“…For more in-depth structural information concerning how hairpin polyamides bind to a target sequence, please refer to [12,13]. It may be presumed that a PA, with a short half-life, binds and inhibits TF activity within 24 hours in culture whereas the biological consequences of altered transcription may lag behind.…”
Section: Results and Discussion: Our Polyamide Follows Established Pairmentioning
confidence: 99%
“…For more in-depth structural information concerning how hairpin polyamides bind to a target sequence, please refer to [12,13]. It may be presumed that a PA, with a short half-life, binds and inhibits TF activity within 24 hours in culture whereas the biological consequences of altered transcription may lag behind.…”
Section: Results and Discussion: Our Polyamide Follows Established Pairmentioning
confidence: 99%
“…[11] Recently, the group of Ghadwal showed that P 2 [6,9,11] units are released upon reaction of a phosphorus analogue of p-quinodimethane [(IPr=C) 2 P 4 ] (IPr = 1,3-bis(2,6-di-isopropylphenyl)imidazolin-2-ylidene) containing a planar P 4 ring with cyclohexadiene. [12] However, this reaction was not selective, affording both P 4 and the cycloaddition product B.…”
Section: Introductionmentioning
confidence: 99%
“…Under mild thermal activation, D releases P 2 which could be detected by molecular beam mass spectrometry and ultimately transforms to red phosphorus [11] . Recently, the group of Ghadwal showed that P 2 units are released upon reaction of a phosphorus analogue of p ‐quinodimethane [(IPr=C) 2 P 4 ] (IPr=1,3‐bis(2,6‐di‐ iso ‐propylphenyl)imidazolin‐2‐ylidene) containing a planar P 4 ring with cyclohexadiene [12] . However, this reaction was not selective, affording both P 4 and the cycloaddition product B .…”
Section: Introductionmentioning
confidence: 99%
“…Sterically demanding substituents further provide kinetic protection, rendering the isolation of such species possible (Scheme ). In particular, our own group could demonstrate the versatile reactivity of the stable four-membered cyclic biradical [P­(μ-NR)] 2 ( 1 , R = Ter [2,6-dimesitylphenyl] or Hyp [tris­(trimethylsilyl)­silyl]), which is based solely on group 15 elements (Scheme ). …”
Section: Introductionmentioning
confidence: 99%